University Harmonization in the European Territory? The Case of Psychology and Biology - Toledo-Lara, Gustavo Eduardo (Revista de Estudios Andaluces, 2018)
In this article one presents an analysis of the condition of the university harmonization in the European Space of Top Education. For such this purpose and from a qualitative perspective, there were examined the declarations of the European secretaries in charge of the university sector, the guiding criteria of the process of Bologna and studied 55 European universities, from the analysis of the degrees of Psychology and of Biology to determine how there is formed the application of the process of Bologna in both cases and to verify, if in effect, the university harmonization has taken place in Europe, or if on the contrary, they have given themselves steps though the harmonization of the university systems still is a hanging task.